Mestre Expedito Ribeiro: materialidade e imaterialidade no fazer escultórico em Minas Gerais na contemporaneidade - Adriano de Souza Bueno (2022)
Since the beginning of the colonization process, sacred production has been part of the spread of Catholic Christianity in Brasil. The activity related to the making of devotional wooden sculptures, initially in monastic environments and continued, a posteriori, by lay people, has the dedication of artisans throughout the national territory until the present day. The present work deals with the analysis regarding the creative process of the contemporary sculptor Expedito Sobreira Ribeiro, Mestre Ribeiro, from the Minas Gerais city of Porto Firme, in Vale do Piranga. For the study, a brief bibliographic review was carried out about the production of devotional wooden sculptures in the colonial period in Minas Gerais, the sculptural technique in wood, the wood itself as a raw material and the main sculpture tools. Through interviews and conversations with the artist, together with the photographic documentation of works and tools, a comparative study was established, from the technical point of view of sculptural making, between the artistic trajectory of the sculptor under study and the 18th century production modes of devotional wooden carvings in Minas Gerais.